Estudio de caso n°593-15-ep/21: análisis de terminación del contrato de trabajo de la mujer embarazada por fenecimiento del plazo - Ruiz Defaz, Armando Josué; Cuzco Pulla, Alexander Armando (Machala, 2022)
The manifest research work analyzes the legal problems of the termination of an occasional work contract due to the expiration of its term in the context of the employment relationship of a pregnant woman. It is developed under the modality of "Case Study No. 593-15-EP/21: Analysis of the Termination of the Employment Contract of the Pregnant Woman Due to Expiration of the Term." The general objective of the work is to establish epistemological criteria that allow solving the legal abstraction that exists in the Ecuadorian legal system regarding the expiry of the term of the occasional employment contract of pregnant women. The aforementioned case is developed from a protection action filed by a pregnant woman against the Ministry of Labor and the Attorney General of the State for the alleged violation of constitutional rights as a result of the termination of the period of time of her occasional employment contract. job. Having identified the object of study, this research has been considered from the perspective of a mixed methodological approach in order to take advantage of the resources of the qualitative and quantitative approach. The main method used as a way of obtaining information within the conceptual delimitation of the subject has been the bibliographical application based on the arguments contained within Judgment No. 593-15-EP/21 of the Constitutional Court of Ecuador and also of the revision of the legal norms such as the Constitution of the Republic, the Labor Code, the Organic Law of the Public Service and its respective Regulation, the doctrine and the jurisprudence of analogous cases have also been considered as a bibliographic source. The investigation exposes from the bases of Roman law the legal nature of occasional work contracts, from an ethical perspective the essence is defined by which this type of atypical contracts have a specific term as a means of protecting the interests of the employer that requires the non-permanent services of a person and on the other hand the interests of the employee who must hold the full rights of the worker for the duration of the employment relationship according to the term agreed and established in the law so that it cannot be exceeded or precarious . The differences and legal effects of the unilateral termination of the contract, the figure of untimely dismissal and the ipso iure termination of the employment relationship are also presented. In addition, the legal criteria of the trial judges who resolved the protection action in law are also addressed, as well as the considerations of the Constitutional Court judges who, at the discretion of this investigation and by virtue of the arguments presented, exceed the limits due to the investment of the iura novit curia principle and denature the immanent qualities of occasional employment contracts by adding exceptions to them as an abbreviated means of solving the problem and avoiding addressing it from its core. Through the conceptual and theoretical analysis, as well as the use of quantification instruments, the scientific foundations are presented that allow us to conclude that the decision reflected in Judgment No. 593-15-EP/21 does not satisfy the legal abstraction regarding the expiry of the term of employment contracts for pregnant women.
El manifiesto trabajo de investigación analiza la problemática jurídica de la terminación de un contrato ocasional de trabajo por fenecimiento de su plazo en el contexto de la relación laboral de una mujer embarazada. Se desarrolla cobre la modalidad de “Estudio De Caso No. 593-15-EP/21: Análisis De Terminación Del Contrato De Trabajo De La Mujer Embarazada Por Fenecimiento Del Plazo.” El objetivo general del trabajo consiste en establecer criterios epistemológicos que permitan solucionar la abstracción legal que existe en el ordenamiento jurídico ecuatoriano en cuanto al fenecimiento del plazo del contrato ocasional de trabajo de la mujer embarazada. El mencionado caso se desarrolla a partir de una acción de protección presentada por una mujer embarazada en contra del Ministerio de Trabajo y el Procurador General del Estado por la presunta vulneración de derechos constitucionales como consecuencia de la terminación del periodo de tiempo de su contrato ocasional de trabajo. Habiendo identificado el objeto de estudio, esta investigación ha sido considerada desde la perspectiva de un enfoque metodológico mixto a fin de aprovechar los recursos del enfoque cualitativo y cuantitativo. El principal método empleado como forma de obtención de información dentro de la delimitación conceptual del tema ha sido la aplicación bibliográfica partiendo de los argumentos contenidos dentro de la Sentencia No. 593-15-EP/21 de la Corte Constitucional del Ecuador y también de la revisión de las normas legales como la Constitución de la República, el Código de Trabajo, la Ley Orgánica del Servicio Público y su respectivo Reglamento, también se han considerado como fuente bibliográfica la doctrina y la jurisprudencia de casos análogos. La investigación expone desde las bases del derecho romano la naturaleza jurídica de los contratos ocasionales de trabajo, desde una perspectiva deontológica se define la esencia por la cual este tipo de contratos atípicos cuentan con un plazo especifico como medio de proteger los intereses del empleador que requiere los servicios no permanentes de una persona y por otra parte los intereses del empleado quien debe ostentar la plenitud de los derechos propios del trabajador en tanto dure la relación laboral de acuerdo al plazo convenido y establecido en la ley de manera que no pueda excederse ni precarizarse. Se presentan también las diferencias y efectos jurídicos de la terminación unilateral del contrato, la figura de despido intempestivo y la terminación ipso iure de la relación laboral. Se abordan además los criterios jurídicos de los jueces de instancia que resolvieron en derecho la acción de protección y también las consideraciones de los jueces de Corte Constitucional que, a criterio de esta investigación y en virtud de los argumentos expuestos, se extralimitan por el investimento del principio iura novit curia y desnaturalizan las cualidades inmanentes de los contratos ocasionales de trabajo al adherirles excepciones como un medio abreviado de solución de la problemática y evitar abordarla desde su parte medular. Por medio del análisis conceptual y teórico, así como, con la utilización de instrumentos de cuantificación se presentan los fundamentos científicos que permiten concluir que la decisión reflejada en la Sentencia No. 593-15-EP/21 no satisface la abstracción legal en cuanto al fenecimiento del plazo de los contratos de trabajo de las mujeres embarazadas.
Keywords: CONTRATO OCASIONAL; MUJER EMBARAZADA; DESPIDO UNILATERAL; PRINCIPIO DE ESTABILIDAD